The apple orchard ebook Bella vista chronicles, book 1. - Wiggs, Susan (Bella Vista Chronicles, 2013)
#1 New York Times bestselling author Susan Wiggs brings readers into the lush abundance of Sonoma County, in a story of sisters, friendship and the invisible bonds of history that are woven like a spell around us. Tess Delaney makes a living returning stolen treasures to their rightful owners. She loves illuminating history, filling the spaces in people's hearts with stories of their family legacies. But Tess's own history is filled with gaps: a father she never met, and a mother who spent more time traveling than with her daughter. Then Dominic Rossi arrives on the doorstep of the San Francisco shop Tess hopes to buy, and he tells her that the grandfather she never knew is in a coma. Tess has been named in his will to inherit half of Bella Vista, a hundred-acre apple orchard in the magical Sonoma town called Archangel. The rest is willed to Isabel Johansen. A half sister she hadn't heard of. Isabel is everything Tess isn't: all softness to Tess's hard angles, warm and nurturing where Tess is tightly wound. But against the rich landscape of Bella Vista, with Isabel and Dominic by her side, Tess begins to discover a world filled with the simple pleasures of food and family, of the warm earth beneath her bare feet. A world where family comes first and the roots of history run deep. "Wiggs tells a layered, powerful story of love, loss, hope and redemption." -- Kirkus, starred review